Synchronous cervical plexus schwannomas: a rare presentation - Zahid, Hira; Mukhtar, Hamid; Khan, Imran Mohib; Shahid, Hamza (Journal of the Pakistan Medical Association, 2025)
Schwannomas are benign neural sheath tumours composed of neoplastic Schwann cells, 25-45% of which occur in the head and neck region. Clinical presentation varies according to the anatomical site but the most common presenting symptoms are a slow growing lesion, painless mass, or neurological deficits. Preoperative workup includes imaging studies e.g., ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI). Management options include observation, surgical excision, intracapsular enucleation and radiotherapy. We present a rare case of synchronous cervical plexus schwannomas in a 13-year-old female. The patient presented with a slow growing mass on the right side of the neck, which had been present since early childhood. A percutaneous biopsy confirmed diagnosis of a schwannoma. Intracapsular enucleation was performed, and perioperative findings revealed two synchronous schwannomas in the right supraclavicular region. Synchronous schwannomas of the cervical plexus is a very rare presentation, with no prior cases reported in the literature. Surgical excision remains the treatment of choice in the management of such cases. Keywords: cervical schwannoma, neck tumour, peripheral nerve sheath tumour, schwannoma, synchronous.